PENGARUH INDEPENDENSI, INTERGRITAS, PROFESIONALISME, KOMPETENSI DAN KEPA TUHAN KODE ETIK TERHADAP KUALITAS AUDIT (Studi Kasus pada Pemeriksa BPK RI Penvakilan Provinsi Jawa Tengab) (Students' Journal of Accounting and Banking, 2014)
The purpose of this research is to analyse the influence of independency, integrity, professionalism, competency and compliance code of conduct on the quality of audit on the auditor BPK RI Representative of Province in Central of Java.The population of this research are all auditor which have followed Education and Training of Functional Posision of Auditor (JFP) and 2 years minimal job experience as auditor. Sampling was conducted using a purposive sampling method and number of samples of 95 respondents. Primary data collection method used is multiple regression model.The result showed that integrity, professionalism and compliance code of conduct have a position impact on audit quality. And independency and competency doesn’t have a position impact on audit quality.Keywords: independency, integrity, professionalism, competency, compliance code of conduct, quality of audit